Energy Efficient Routing in MANET: A Survey (International Journal of Engineering and Computer Science, 2014)
Mobile Ad Hoc networks (MANET) allow a set of wireless hosts to exchange information without any special infrastructure. Limited battery power is one of the most important issues in mobile ad-hoc network by that efficient utilization of battery power or energy is must in routing process. Among the various factors which cause disorder in such a network and routing process the problem of broken links is occur due to the lack of energy is the most important ones. Due to the unawareness of energy of mobile nodes that problem will occur. The numbers of mobile nodes that are take part in communication are aware about the energy statue of rest of the mobile nodes then energy efficient routing approaches will maintain the network condition so that the packet can be delivered reliably without any link failure. There are lot of work has been done in this field and some of them are proposed a good approaches. Now in this paper we presents the some latest approaches that are reduces the energy consumption of mobile nodes and increases the life time of battery by that also enhance the life of network.